(ISC)2 CISSP Certified Information Systems Security Professional Official Study Guide. : 2021. - Chapple, Mike, ....-; Stewart, James Michael, ....-; Gibson, Darril, ....- (New Jersey : John Wiley & sons, 2021)
(ISC)² CISSP Study Guide, 9th Edition has been completely updated for the latest 2021 CISSP Body of Knowledge. This bestselling Sybex study guide covers 100% of all exam objectives. You'll prepare for the exam smarter and faster with Sybex thanks to expert content, real-world examples, advice on passing each section of the exam, access to the Sybex online interactive learning environment, and much more. Reinforce what you've learned with key topic exam essentials and chapter review questions.
Media Storage Facilities.
Description based on publisher supplied metadata and other sources.
Keywords: Electronic books; beveiliging; software